2007
DOI: 10.1007/s10461-007-9302-z
|View full text |Cite
|
Sign up to set email alerts
|

Why Housing?

Abstract: Housing/lack of housing and HIV are powerfully linked. Housing occupies an important place in the causal chains linking poverty and inequality, and HIV risk and outcomes of infection. The articles in this Special Supplement of AIDS and Behavior confirm the impact of homelessness, and poor or unstable housing, on HIV/AIDS, and challenge scientists to test and policy makers to implement the promise of housing as an innovative response to the epidemic. In order to influence the development of policies on housing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 54 publications
(40 reference statements)
2
67
1
Order By: Relevance
“…Research shows that housing or lack of housing and HIV are powerfully linked. 24 Among individuals who engage in HIV risk behaviors, high rates of depression have been found. 25,26 We found that while older age was associated with having fewer sexual partners, it increased the odds of having a risky sexual partner.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that housing or lack of housing and HIV are powerfully linked. 24 Among individuals who engage in HIV risk behaviors, high rates of depression have been found. 25,26 We found that while older age was associated with having fewer sexual partners, it increased the odds of having a risky sexual partner.…”
Section: Discussionmentioning
confidence: 99%
“…Homeless persons are at increased risk of HIV infection and homelessness negatively affects the health of PLWHA (Aidala and Sumartojo 2007;Kidder et al in press;2007a;Shubert and Bernstine 2007;Wolitski et al 2007). Homeless and unstably housed PLWHA may be more likely to experience HIV-related stigma, but little is known about how different subgroups of PLWHA experience HIV stigma.…”
Section: Introductionmentioning
confidence: 99%
“…A major focus of past research regarding sexual risk behaviours has been on individual-level characteristics (Aidala & Sumartojo, 2007;Sumartojo, 2000), or what Susser (1998) and Aidala and Sumartojo (2007) call the black box paradigm and risky person paradigm, respectively. In the context of sexual risk behaviours, the risky person paradigm involves investigating individual-level characteristics that are associated with risk behaviours, which may then lead to acquiring STIs and homelessness.…”
Section: From Individual To Structural Determinantsmentioning
confidence: 99%
“…In recent years, however, increasing attention has been given to the importance of structural factors that impact sexual risk behaviours (Aidala et al, 2005;Auerbach, 2009;Evans, Jana, & Lambert, 2010;Lippman et al, 2012;Seeley et al, 2012;Steen, Wi, Kamali, & Ndowa, 2009 (Sumartojo, 2000, p. S3) that are mostly outside of the individual's immediate control (Aidala & Sumartojo, 2007;Blankenship, Friedman, Dworkin, & Mantell, 2006). …”
Section: From Individual To Structural Determinantsmentioning
confidence: 99%
See 1 more Smart Citation